A study on coupling and coordination of grain production and agricultural ecological protection in the Yangtze river economic belt - Xuanzhu Meng; Linqi Liu; Yingying Cai; Xinyue Wang (Ciência Rural)
ABSTRACT: The Yangtze River Economic Belt is an important grain production area and ecological reserve in China. It is of great practical significance to promote coordinated development between grain production and agricultural ecological protection in this region. This paper analyzed the coupling and coordination of grain production and agricultural ecological protection in the Yangtze River Economic Belt during 2009-2018 based on entropy weight method and coupling coordination model. The results showed that on the whole, comprehensive indexes of the two systems show a trend of first declining and then rising, the development stage of coupling and coordination has entered good coordination stage from primary coordination stage, and the development type of coupling and coordination belongs to the lag of agricultural ecological protection. In terms of regions, Guizhou has the highest comprehensive level of grain production, and Anhui has the lowest; the region with the highest comprehensive level of agricultural ecological protection is Chongqing, and the lowest is Jiangxi; only Anhui and Hubei have entered high coordination stage, and only Shanghai, Zhejiang, Chongqing, and Yunnan belong to the type of synchronous development. The results make up for the lack of research on coupling and coordination between grain production and agricultural ecological protection, and provided, a feasible development path for exploring coordinated development of grain production and agricultural ecological protection in the Yangtze River Economic Belt.